The Use of Supplementary Materials in EFL classes: A comparative analysis of public and private High School - Aguilar Galarza, María José (2012)
The use of supplementary materials in ELF classes: a comparative analysis of public and private high schools is the present study investigated. The main goal of the research is to find out whether or not teachers use supplementary materials, and if they are used how pertinent, appropriate, and qualified those materials are. This research took place in a private and a public high school; both are located in rural area of the Metropolitan District of Quito, Ecuador. The sample of one hundred fifty four students in 1st, 2nd and 3rd of high school of both schools. The data collection was obtained by note-taking, and observation formats and surveys. The principal methods to analyze the data after classes’ observation were Quantitative approach and Qualitative approach. The result shows that the use of supplementary materials was different in frequency and variety in both schools. The use of supplementary material in public high school was the white board in contrast to private high school that uses handouts, pictures or stories. Generally, the used of them were pertinent, appropriate and were of good quality.